The impact of foreign direct investment towards services and agricultural sectors in Malaysia / Siti Furhanah Ulfah Ali Akbar - Ali Akbar, Siti Furhanah Ulfah (2012)
This paper is to determine the implication of foreign direct investment (FDI) towards two different sectors in Malaysia and also to determine which of these sectors affected more by the FDI. We are focusing on services and agricultural sectors in Malaysia which give so much benefit to country and also the FDI to achieve the objectives of the study. Based on this study, simple-regression analysis had been used to measure the significant of the variables. This study is using the time series data from 1980 to 2010. The methods that we used to examine the aim of this study are Unit Root Test and Ordinary Least Squared (OLS). As conclusion, the result shows that there is a positive relationship of both independent variables with the FDI and the most affected by the FDI was the services sectors.